Deep Learning for Lung Disease Diagnosis: A CNN-Based Radiographic Approach: Deep Learning for Lung Disease Diagnosis - Danang Bagus Wibowo; Fauzan, Achmad (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
Various types of lung diseases affect the human respiratory system, with pneumonia, tuberculosis, and Covid-19 being among the most common. Early detection plays a crucial role in improving treatment outcomes and reducing mortality rates. Chest X-ray imaging is one of the most widely used diagnostic methods; however, it typically relies on manual interpretation by medical professionals, which can be time-consuming and prone to inconsistencies. This study aims to apply the Convolutional Neural Network (CNN) method as an automated approach to classify chest X-ray images of lung conditions. The dataset consists of 460 X-ray images for each category: normal, pneumonia, tuberculosis, and Covid-19. The CNN model was trained using an input shape of 224×224 pixels, a 3×3 filter size, and 5 epochs. Evaluation results showed that the model achieved 97% accuracy on the validation and 93% on the testing data. These findings highlight the potential of CNN in supporting automated diagnosis of lung diseases. In the future, this technology is expected to assist healthcare professionals in delivering faster and more accurate diagnoses, particularly in areas with limited access to radiology experts. Moreover, this innovation aligns with Sustainable Development Goal (SDGs) 3: Good Health and Well-being, by promoting early detection, timely treatment, and more equitable access to quality healthcare services.